Alveolar Echinococcosis (AE) :An Important Neglected Foodborne Pathogen Threatening Community Health - Bahador Hajimohammadi; Emad Ahmadiara (Shahid Sadoughi University of Medical Sciences, 2017)
Alveolar echinococcosis (AE) caused by Echinococcus multilocularis can infect humans as a dead-end host. They matured in canid’s intestine (e.g. foxes, jackals, wolves, dogs, cats, etc.). AE is seen across the world. It has a high prevalence in the central and northern parts of Europe, North America and Asia. The prevalence of AE was low in the past, even in hyper endemic regions. But in recent decade, unfortunately, it seems to increase and spread rapidly. One of the most important reasons is the development and expanding of cities and villages, which lead to jackals and foxes colonization and migration to urban locations. This helps them to have closer connection with human population, canids and other appropriate hosts for dispreading the infection. In the present study, we discuss about the life cycle of E. multilocularis and its etiology and epidemiology as an important neglected zoonotic parasite. In canid as final hosts, infection is not malignant and significant clinical signs are usually never seen, unless in very unusual heavy infections. However, in contrast, infection in humans is very dangerous, and even more serious than another widespread species, Echinococcus granulosus that causes cystic echinococcosis (CE) (1). ....